(NpOWESTI I RASSKAZY(B: [1917-1944] / s (N~ASTX (B2s - (NtOLSTOJ(B, (NaLEKSEJ nIKOLAEWI^s ((NlENINGRAD(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1979)
(NwO WTOROJ TOM WHODQT (B"(NrASSKAZ PROEZVEGO ^ELOWEKA(B", "(NdETSTWO nIKITY(B", "(NgOLUBYE gORODA(B", "(NgAD@KA(B", "(NrASSKAZY iWANA sUDAREWA(B" (NI DRUGIE(B, (NNAPISANNYE W (B1917-1944 (NGODAH(B.s
rus
Keywords: (NpOWESTX(B, (NRASSKAZYs